Different Proteostasis Mechanisms Facilitate the Assembly of Individual Components on the Chitin Synthase 3 Complex at the Endoplasmic Reticulum - Noelia Sánchez; Rosario Valle; César Roncero (Journal of Fungi)
Chitin synthase 3 complex assembly begins at the endoplasmic reticulum where the formation of a Chs3/Chs7 complex facilitates its exit from the ER and its transport along the secretory route. In the present study, our work shows that orphan molecules of Chs7 can exit the ER and are later recycled from the early Golgi by coat protein I (COPI) machinery via the adaptor complex Erv41/Erv46. Moreover, an eventual excess of the protein in the Golgi is recognized by the GGA complex and targeted to the vacuole for degradation through the ESCRT machinery. Non-oligomerizable versions of Chs3 can also exit the ER individually and follow a similar route to that of Chs7. We therefore demonstrate the traffic of unassembled CS3 subunits and describe the cellular mechanisms that guarantee the correct assembly of this protein complex at the ER while providing a default traffic route to the vacuole in case of its failure. This traffic route is shared with canonical ER adaptors, such as Erv29 and Erv14, and other components of protein complexes. The comparative analysis of their traffic allows us to discern a cellular program that combines COPI recycling, proteasomal degradation, and vacuolar disposal for maintaining protein homeostasis at the ER.